Revisiting the Contribution of Islamic Banks’ Financing to Economic Growth: The Indonesian Experience - Indri Supriani; Bayu Arie Fianto; Najim Nur Fauziah; Ryan Rahmah Maulayati (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The contribution of Islamic banking towards economic growth remains debatable amongst academicians and practitioners. This study investigates the relationship between Islamic banks’ financing and economic growth in Indonesia which is the largest Muslim population country. This study adopts Autoregressive-Distributed Lag (ARDL) and utilizes time-series quarterly data from 2011Q1 to 2019Q3. The study uses four predictors: financing to deposit ratio, gross capital fixed formation, inflation, and trade openness. The results from the auto-regressive distributed lag model indicate that, in the long-run, Islamic banks' financing has a significant impact on the Indonesian economy. However, in the short-run, financing does not make a substantial contribution to Indonesian economic growth. The study’s key implication is that financing by Islamic banks still makes a limited contribution to economic growth in Indonesia. This study enhances the literature review, specifically on evaluating the contribution of Islamic banks towards economic growth. Numerous existing studies on this topic covering the crisis period data, which might suffer from data bias. Therefore, this study addresses this topic, excluding the global financial crises period such as 1998, 2008, and 2020, to demonstrate Islamic banks' evident contribution to Indonesian economic growth.